Desenvolvimento de aplicação para internet para análise estrutural de pórticos planos - Fontes, Marcos Dinei Medeiros (2023)
Through mathematical models, it is possible to simulate the behavior of structures, systems, and processes, enabling the prediction and optimization of their performance. In this context, Matrix Structural Analysis is used to model the structure as a set of interconnected elements, and the Stiffness Method is employed to determine the forces and displacements of the structure's elements. This monography introduces the development of an internet application based on these methods, with a focus on the analysis of planar frames, which are structures composed of interconnected straight elements at nodes. Through the application, users can define the properties of the structure's elements, such as length, cross-sectional area, moment of inertia, and material characteristics, as well as boundary conditions like supports and applied loads. The application was developed using JavaScript and HTML technologies, enabling users to input structure data and visualize analysis results interactively and intuitively. The application's interface was designed to be simple and user-friendly, accessible from any device due to its responsiveness, allowing users to easily define the properties and conditions of the structure